A Cross-sectional Study to Assess the Association of Minor Criteria of Hannifin and Rajka with Age and Gender in Pediatric Atopic Dermatitis Population - Garima Bansal; Rishi Bansal (Indian Journal of Paediatric Dermatology)
Background: Atopic dermatitis (AD) is a chronic relapsing dermatitis characterized by intense itching. Hanifin and Rajka criteria are the most commonly used diagnostic criteria in hospital setup, consisting of 4 major and 23 minor criteria. Objectives: The objective of the study was to estimate the frequency of distribution of Hanifin and Rajka minor criteria in the pediatric age group, to assess the association of age with minor criteria of AD, and to assess the association of gender with minor criteria of AD. Materials and Methods: A cross-sectional study of 150 pediatric patients (≤16 years) was conducted in the department of dermatology, who were diagnosed with AD based on history and clinical and ophthalmological examination. Serum immunoglobulin E (IgE) was also assessed. The age and gender analysis were done using a Chi-square test. Results: The most common clinical features were orbital darkening 133 (88.7%), Dennie–Morgan infraorbital fold 126 (84%), xerosis 102 (68%), keratosis pilaris 101 (67.3%), and hyperlinear palm 98 (65%). Serum IgE was elevated in 26%. The majority presented with high readings with no obvious keratoconus. Male children (88%) presented predominantly with orbital darkening (90.9%) and had an exacerbation in winters (18.2%) in comparison to females (62%) P ≤ 0.05. Children >1 year (141%) presented mostly with keratosis pilaris (71.6%), nonspecific hand-foot dermatitis (49.6%), and facial erythema (34.8%) than in infants (9%) P ≤ 0.05. Conclusion: Minor criteria are useful for the diagnosis of AD. Male children are more affected and manifest with orbital darkening with Dennie–Morgan infraorbital fold as the chief clinical finding in both the groups. Factors such as ethnic/racial, environmental, and diet have a role in AD.